Effects of Mind‐Body Exercises on Cognitive Function in Older Adults: A Meta‐Analysis. Issue 4 (18th December 2018) - Wu, Chunxiao; Yi, Qu; Zheng, Xiaoyan; Cui, Shaoyang; Chen, Bin; Lu, Liming; Tang, Chunzhi
Abstract : BACKGROUND/OBJECTIVES: Mind‐body exercise has positive effects on cognitive performance, according to clinical observation and experts' recommendations. However, its potential benefits for the cognitive function of aging adults are uncertain and still lack systematic estimations. Therefore, we conducted a systematic review and meta‐analysis to evaluate the overall efficacy and effectiveness of mind‐body exercises for cognitive performance in aging individuals with or without cognitive impairment. DESIGN: A systematic review and meta‐analysis. SETTING AND PARTICIPANTS: We searched related trials through June 2018 from four databases: Medline, Embase, PsycINFO (all via Ovid), and the Cochrane Library/Central Register of Controlled Trials. MEASUREMENTS: Methodological quality was assessed using the Cochrane Risk of Bias Tool. A meta‐analysis of comparative effects was performed using Review Manager v.5.3 software, and publication bias was examined using Egger's test. RESULTS: A total of 32 randomized controlled trials with 3624 participants were ultimately included in this meta‐analysis. The results revealed that mind‐body exercises as a whole had benefits in improving global cognition compared with that of the control group (mean difference [MD] = 0.92; 95% confidence interval [CI] = 0.33‐1.51; p = .002) and were more effective than control interventions in promoting cognitive flexibility (MD = −8.80; 95% CI = −15.22 to −2.38; p = .007), working memory (MD = 0.32; 95% CI = 0.01‐0.64; p = .05), verbal fluency (standardized mean difference [SMD] = 0.27; 95% CI = 0.09‐0.45; p = .003), and learning (SMD = 0.24; 95% CI = 0.10‐0.39; p = .001) on cognitively intact or impaired older adults. In dose‐subgroup analysis, only moderate exercise intensity (60‐120 min per week) significantly increased global cognition scores compared with those of the control group (MD = 1.15; 95% CI = 0.34‐1.97; p = .006). CONCLUSION: Mind‐body exercises, especially tai chi and dance mind‐body exercise, are beneficial for improving global cognition, cognitive flexibility, working memory, verbal fluency, and learning in cognitively intact or impaired older adults. Moderate intensity is recommended as the optimal dose for older adults. J Am Geriatr Soc 67:749–758, 2019.